2021
DOI: 10.1186/s12879-020-05693-1
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of diarrhea by multiplex polymerase chain reaction among young children in the United Arab Emirates: a case-control study

Abstract: Background Little is known about the etiology of childhood diarrhea in the United Arab Emirates (UAE) especially after the introduction of rotavirus vaccines. This study aimed to identify gastrointestinal pathogens in children with diarrhea (cases) and the carriage rate of these pathogens in asymptomatic children (controls). Methods Stool samples were collected from 203 cases and 73 controls who presented to two major hospitals in Al Ain city, UAE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…We could not find relevant studies published in the following five countries: the Comoros Islands, Djibouti, Mauritania, Somalia, and Syria. Eleven studies were conducted in Middle East countries, namely: Iraq ( n = 2) [ 35 , 36 ], Jordan ( n = 2) [ 37 , 38 ], Kuwait ( n = 2) [ 39 , 40 ], Yemen ( n = 2) [ 41 , 42 ], Bahrain ( n = 1) [ 43 ], Lebanon ( n = 1) [ 44 ], and the United Arab Emirates ( n = 1) [ 45 ]. Whereas 10 studies were from North African countries, namely: Egypt ( n = 3) [ 46 , 47 , 48 ], Morocco ( n = 2) [ 49 , 50 ], Sudan ( n = 2) [ 51 , 52 ], Algeria ( n = 1) [ 53 ], Libya ( n = 1) [ 54 ], Tunisia ( n = 1) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not find relevant studies published in the following five countries: the Comoros Islands, Djibouti, Mauritania, Somalia, and Syria. Eleven studies were conducted in Middle East countries, namely: Iraq ( n = 2) [ 35 , 36 ], Jordan ( n = 2) [ 37 , 38 ], Kuwait ( n = 2) [ 39 , 40 ], Yemen ( n = 2) [ 41 , 42 ], Bahrain ( n = 1) [ 43 ], Lebanon ( n = 1) [ 44 ], and the United Arab Emirates ( n = 1) [ 45 ]. Whereas 10 studies were from North African countries, namely: Egypt ( n = 3) [ 46 , 47 , 48 ], Morocco ( n = 2) [ 49 , 50 ], Sudan ( n = 2) [ 51 , 52 ], Algeria ( n = 1) [ 53 ], Libya ( n = 1) [ 54 ], Tunisia ( n = 1) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in this review, a total of 14 studies were carried out among children less than five years of age. The prevalence of HAdV infections among children less than 5 years old was reported in the included studies as follows: Iraq, 14/320 (4.5%) [ 36 ]; Iraq, 3/100 (3%) [ 35 ]; Jordan, 54/350 (15.4%) [ 37 ]; Kuwait, 27/743 (3.6%) [ 40 ]; Yemen, 36/326 (11%) [ 41 ], United Arab Emirates, 35/203 (17.2%) [ 45 ], Egypt, 8/119 (6.7%) [ 48 ], Egypt, 20/100 (20%) [ 46 ], Egypt, 17/60 (28.3%) [ 47 ], Morocco, 119/700 (17%) [ 49 ], Sudan, 7/437 (1.6%) [ 52 ], Algeria, 9/117 (7.5%) [ 53 ], Libya, 17/239 (7.1%) [ 54 ], and Tunisia, 3/583 (19.6%) [ 55 ]. The remaining studies reported HAdV infections among older children.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in virulence between recombinant viruses compared to non-recombinant viruses is under investigation but hampered by the lack of tools for evaluation [141,[145][146][147][148]. Co-infection with other AGE viruses, bacteria and parasites are also common and understudied [137,[149][150][151].…”
Section: Virus Backgroundmentioning
confidence: 99%
“…HAstV infection mainly occurs during the dry season in the African continent; meanwhile, the highest occurrence reported in the tropical areas is often in the rainy season and winter season in temperate climate countries [ 47 , 49 ]. Patients usually manifested with diarrhoea, fever, vomiting, and abdominal pain [ 48 , 50 ].…”
Section: Causative Agents Of Agementioning
confidence: 99%